The politics of refusal: Aboriginal sovereignty and the Northern Gateway pipeline. (22nd November 2016) - Wood, Patricia Burke; Rossiter, David A.
Abstract: This study examines the politics of Aboriginal title in British Columbia in the context of the approval process for the Northern Gateway pipeline proposal. We highlight presentations made by First Nations representatives and individuals during the Community Hearings for Oral Evidence stage of the Joint Review Panel, as well as the political actions of First Nations governments, organizations, and individuals outside the hearings. Speakers from several different nations articulated common points with regard to territory, property, and place in support of a case for sovereignty. Building from Aboriginal political theory, we argue that the evidence supports a reading of Aboriginal positions on the pipeline as a politics of refusal, the starting point of which lies within Aboriginal knowledge and governance systems, and not mere reaction to the development proposal. We hope to see more critical geographies of natural resource development incorporate Aboriginal theory into their frameworks. La politique du refus : la souveraineté autochtone et l'oléoduc Northern Gateway: Cette étude s'intéresse aux questions politiques portant sur les droits territoriaux des Autochtones en Colombie‐Britannique qui émergent du processus d'approbation du projet d'oléoduc Northern Gateway. Nous proposons un survol des différents exposés des représentants et individus des Premières nations entendus lors de la phase des Audiences communautaires pour la présentation de la preuve orale de la Commission d'examen conjoint, ainsi que les actions politiques réalisées par des gouvernements, organisations et individus des Premières nations en parallèle aux audiences. Des conférenciers provenant de différentes nations ont fait ressortir les mêmes points en ce qui concerne le territoire, la propriété et le lieu en démontrant le bien‐fondé de la souveraineté. Prenant comme base la théorie politique autochtone, nous faisons valoir que les témoignages recueillis indiquent que les positions autochtones sur l'oléoduc s'inscrivent dans une politique du refus dont la source se trouve dans les systèmes de savoir et de gouvernance autochtone, et non dans une simple réaction à la proposition de projet. Il est souhaitable que la théorie autochtone occupe une place centrale dans les perspectives critiques en géographie du développement des ressources naturelles. Key Messages: Claims of Aboriginal sovereignty over territory crossed by proposed pipeline are substantive and practised, and well‐grounded in Canadian law. Aboriginal presentations to the Joint Review Panel are examples of a politics of refusal based in Aboriginal knowledge, governance, experience, and perspective, rather than merely a response to a specific proposal. Geographic research on natural resource development would benefit from more incorporation of Aboriginal theory.